Case Report: Concurrent Resistance and Aerobic Training Regulate Adiponectin Expression and Disease Severity in Multiple Sclerosis: A Case Study - Grazioli, Elisa; Nigro, Ersilia; Cerulli, Claudia; Borriello, Giovanna; Mancini, Annamaria; Tranchita, Eliana; Polito, Rita; Parisi, Attilio; Buono, Pasqualina; Daniele, Aurora (Frontiers in Neuroscience, 2020)
Adapted exercise is an effective nonpharmacological tool to improve functional, cognitive and psychological parameters in Multiple Sclerosis (MS), in association with increased Quality of life (QoL) and decreased disease severity. Adipose tissue, through the production of different adipokines, is involved in regulating energy metabolism and inflammation. Adiponectin, increased in MS, circulates as oligomers of Low (LMW), Medium (MMW) and High Molecular Weight (HMW), the latter mediating the main biological effects. The aim of study was to evaluate the effects of 4 months training at moderate intensity (65% Heart Rate Reserve) on BMI, adiponectin and QoL in a volunteer with secondary progressive MS. The parameters were evaluated before (T0), after 4 months training (T1) and six months after the end of training (T2); total serum adiponectin and its oligomeric profile were evaluated. We found a reduction in BMI (-0.9%) and FAT (-2.6%), an improvement in perceived QoL and a reduced expression of total adiponectin and High Molecular Weight (HMW) oligomers together with decreased MS disability level at T1 measured by EDSS. Despite the limitations of a case study, this represent a starting point to understand the influence of exercise in MS and the relationship with adiponectin expression.